Prevalence and effects of antidepressants during pregnancy on infant outcomes among women in Iceland - Thelma Smáradóttir 1991- (2020)
Objective: Previous studies have suggested that antidepressant use during pregnancy can have adverse negative effects on the infant. Latest studies have shown that the use of antidepressants during pregnancy is increasing. Therefore, the aim of this study was to examine the prevalence and effects on infant outcomes associated with antidepressant use during pregnancy in Iceland. Method: The research design of the study was retrospective cohort study using a database from the medical journal system at the National University Hospital of Iceland. The study included data on all mothers who gave birth between December 2018 and December 2019, in total 3.327 mothers and their singleton alive infants. Results: Icelandic mothers of the study cohort who used any antidepressant medication during pregnancy were in total 324 (9.7%). The mean age of the mothers was 30.5, the majority was Icelandic (83.6%) and had a university degree or was studying at university level (55%). Infants exposed to antidepressants during pregnancy had significantly lower Apgar score (after one and five minutes) and were born after shorter gestational length compared to infants not exposed to antidepressants. Antidepressant use during pregnancy was not associated with preterm birth, low birth weight, fetal distress or risk of increased observation following delivery. Conclusion: We found that infants exposed to antidepressants during pregnancy are at increased risk of lower Apgar score and shorter gestational length. The prevalence of antidepressant use during pregnancy in Iceland has increased in the recent years. Key words: antidepressants, pregnancy, infant outcomes, Apgar, gestational length, depression.